VD_FINDINFO HC / 2021 / 882 vom 9. Dezember 2021 - VD Tribunal cantonal (2021)
PROTECTION DE L'UNION CONJUGALE, ADMISSION PARTIELLE, RENTE D'INVALIDITÉ, RENTE COMPLÉMENTAIRE{AVS/AI} | 179 al. 1 CC, 285 CC, 285a al. 3 CC